(untitled) (International Journal of Islamic Business, 2016)
The implementation of good governance practices for Islamic products and services is significantly important in order to ensure its sustainability in the long-run. Furthermore, the strong regulatory framework of governance structures which is based on Shari’ah principles can help to reduce fraud, dishonesty and other unethical practices in doing businesses. Nevertheless, for a new Islamic product such as Islamic real estate investment trust, lack of specific standards and guidelines stated for the appointment of Shari’ah Advisor (SA) may distort the optimum growth and future development of this product. Thus, this paper examine the practice of selecting Shari’ah Advisory Committee by Islamic REIT companies in Malaysia using five standard governance framework which are independence, confidentiality, competence, consistency and disclosure. The data are taken from the Islamic REITs’ companies’ annual reports and interviews with relevant authorities such as Bank Negara Malaysia and Securities Commission Malaysia. Results from this study suggest that information of Shari’ah Advisory Board/Committee members and qualifications are not properly disclosed in the annual report and the term of appointment of Shari’ah Advisory Committee in some of the REIT companies is too long. In addition, the elements of Islamic auditing or reporting are vague. These factors are significantly important as they show the important role of good governance in ensuring the faith of investors is not being compromised and the Islamic REIT is Shari’ah compliant. Thus, it can be concluded that more effort need to be put forward in producing a good Islamic governance framework for Islamic REIT.